Externalización o outsourcing hospitalario: Electromedicina. - Lejeune, Joaquín; Román, José R. (Revista Mexicana de Ingenieria Biomedica, 2000)
In this paper, we analyze the advantages of outsourcing and the possible problems that may come up as a result of outsourcing electromedicine in a hospital. The lack of coordination, objectives or flexibility in the customer-supplier relationship, are some of the problems. We also study some tools such as benchmarking and process re-engineering. We conclude with some recommendations to avoid the above-mentioned problems.